Physicochemical Qualities and Health Risk Assessment of Heavy Metals in Drinking Water From Selected Areas of the Gofa Zone, Ethiopia - Atose Duka Dube; Camerun Kastro Kanido (Journal of Chemistry)
Spring and well waters are among the most important sources of drinking water in Gofa Zone rural areas; therefore, it is vital to evaluate the quality of these water sources. Hence, this study aims to determine the physicochemical parameters and metallic mineral concentration with its associated health risks of drinking water in selected rural areas of the Gofa zone, Ethiopia. The purposive sampling method was used for water sample collection. Standard analytical procedures were used to determine the physicochemical parameters and mineral contents. The average values of all physicochemical parameters of spring and well-drinking water of the selected areas were obtained as temperature (20.73°C and 20.30°C), pH (7.2 and 6.07), electrical conductivity (481.13 µS/cm and 584.24 µS/cm), dissolved oxygen (4.09 and 6.07 mg/L), turbidity (1.60 NTU and 6.55 NTU), total dissolved solids (330.83 and 338.3 mg/L), total suspended solids (84.76 and 89.24 mg/L), chloride concentrations (58.15 and 60.47 mg/L), SO42− ion (68.50 mg/L and 5.58 mg/L), NO3+ ion (3.25 and 2.75 mg/L), and fluoride ion concentration (0.49 mg/L and 0.37 mg/L). Health risk assessment indicates that Co metal showed high hazard indices compared with Fe, Cu, and Zn. Additionally, the values of the heavy metal pollution index (MPI) and heavy metal evaluation index (HEI) indicate that the Sawla Kusti spring water (SSW5), Geze Gofa Mhirzho Wola spring water (GGSW7), and Geze Gofa Bulki Guya well water (BGWW8) sources are considered highly polluted and not recommended for drinking purposes.